Trigeminal neuralgia as nonodontogenic toothache: a case report / Yoshinobu Shoji - Shoji, Yoshinobu (Faculty of Medicine, 2021)
Toothaches typically originate from the odontogenic structures such as dentin, pulp and periodontium. Toothaches which have an odontogenic origin are managed effectively in the dental clinic; however, toothaches with a nonodontogenic origin are often difficult to identify. This article presents a case of trigeminal neuralgia that was misdiagnosed as pain of odontogenic origin and initially treated surgically and endodontically, despite no abnormality detected in the physical examination or X-ray. The aim of this article is to present a case of trigeminal neuralgia that may mimic odontogenic toothache. This case highlights the importance of having thorough knowledge and the appropriate clinical skills to differentiate both odontogenic and nonodontogenic toothaches, as well as the need for careful diagnosis before undertaking any treatment.